Relationship between stage of chronic liver disease and thrombocyte functions - Muhsin KAYA; Aylin YAMAN; Şule Mine YAMAN; Nazmiye KURŞUN; Selim KARAYALÇIN (Turkish Journal of Gastroenterology, 2019)
-